2019
DOI: 10.18203/2320-6012.ijrms20190331
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of socio-clinical profile of paediatric TB cases admitted to tertiary health care centre, Odisha, India

Abstract: Background: Tuberculosis is continued to be a major killer of mankind. Childhood tuberculosis contributes to high mortality due to diagnostic difficulty. Different social factors are responsible for its causation. The objective of the study was to assess the socio clinical factors prevalent among paediatric TB cases admitted to MKCG Medical College.Methods: It was a cross sectional study carried out in the indoor paediatric ward of MKCG medical college. Duration of the study was from August 2016 to July 2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…The median age was 7 years. The findings of the present study are comparable with the studies by Parsuram Jena et al [5] and Dr Kalpana Nenavath et al [6], in which the median age was 8 years and 7.9 years, respectively. The study done by Muley et al [7] showed that children above 10 years accounted for 38 %, while it accounted for 39 % in our study.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The median age was 7 years. The findings of the present study are comparable with the studies by Parsuram Jena et al [5] and Dr Kalpana Nenavath et al [6], in which the median age was 8 years and 7.9 years, respectively. The study done by Muley et al [7] showed that children above 10 years accounted for 38 %, while it accounted for 39 % in our study.…”
Section: Discussionsupporting
confidence: 92%
“…In studies conducted by Muley et al [7] and Sultana AT et al [8], the common age group were <6 years and <5 years, respectively. In the present study, the gender distribution was almost equal, with male to female ratio being 1:1.02, which was comparable with the cross-sectional studies done by Parsuram Jena et al [5] and Ashok Garg et al [9], in which males accounted for 54 % and 52 %, respectively. The studies done by Muley et al [5], Sultana AT et al [8] and Anmol Goyal [10] showed that there was male preponderance.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations